2009
DOI: 10.1111/j.1365-2982.2008.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

IL1β‐ and LPS‐induced serotonin secretion is increased in EC cells derived from Crohn’s disease

Abstract: Gut mucosal enterochromaffin (EC) cells are regarded as key regulators of intestinal motility and fluid secretion via secretion of serotonin (5HT), are increased in numbers in mucosal inflammation and located in close proximity to immune cells. We examined whether interleukin (IL)1β and Escherichia coli lipopolysaccharide (LPS) induced EC cell 5HT release through Toll-like/IL-1 (TIL) receptor activation, nuclear factor kappa B (NFκB) and mitogen-activated protein kinase (MAPK) phosphorylation and evaluated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 70 publications
2
114
0
1
Order By: Relevance
“…Macroscopically "normal" tissue obtained from patients undergoing surgery for diverticulitis (n ϭ 3) or colon cancer (colon: n ϭ 4) (all tissue collected between 2009 and 2011 at Yale University, Department of Surgery and designated by the IRB as nonhuman subjects research). EC cells (Ͼ98% purity) were isolated by mucosal stripping, enzymatic digestion, and a combination of Nycodenz gradient fractionation and fluorescence-activated cell sorting as described (27). Approximately 1 ϫ 10 6 cells were obtained per mucosal sample, a quantity sufficient for real-time PCR, short-term culture, and Western blots.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Macroscopically "normal" tissue obtained from patients undergoing surgery for diverticulitis (n ϭ 3) or colon cancer (colon: n ϭ 4) (all tissue collected between 2009 and 2011 at Yale University, Department of Surgery and designated by the IRB as nonhuman subjects research). EC cells (Ͼ98% purity) were isolated by mucosal stripping, enzymatic digestion, and a combination of Nycodenz gradient fractionation and fluorescence-activated cell sorting as described (27). Approximately 1 ϫ 10 6 cells were obtained per mucosal sample, a quantity sufficient for real-time PCR, short-term culture, and Western blots.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were performed on the continuously growing EC cell tumor-derived KRJ-I cells, a model for normal EC cells (6,28), as well as isolated, short-term cultured human ileal EC cells isolated as described (27). HIF signaling pathway activation was measured using transient transfection with Renilla luciferasehypoxia transcriptional response element (HRE) constructs in cells exposed to hypoxia, defined as 0.5% O 2 (maximally responsive effective concentration; Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, it is unclear if the altered distribution of serotonin and CgA in C. trachomatis infected EEC is induced by the bacteria themselves or is part of an innate immunity response via up-regulation of toll-like receptors. Others have reported increased LPSinduced serotonin secretion in EEC derived from patients with Crohn's disease (Kidd et al, 2009). TLR4 stimulation with its agonist LPS also caused the release of human β-defensin-2 (HBD-2) from EEC (Palazzo et al, 2007) and elevated HBD-2 levels have recently been found in patients with IBS (Langhorst et al, 2009).…”
Section: Infection Of Enteroendocrine Cell Linesmentioning
confidence: 98%